Simulation of Electromagnetic Waves Propagating inside Cylinder in Free Space using Finite Difference Time Domain (FDTD) Technique - Farhat, Sedig S. (The Libyan Journal of Science, 2020)
In this paper, we consider the electromagnetic waves propagating inside empty cylinder by utilizing the finite-difference time-domain (FDTD) technique. The cylinder is made of a perfect electric conductor (PEC) placed in a domain in free space. The FDTD technique utilized in this study for solving Maxwell’s time dependent curl equations for a one, two and three dimensions in order to make a comparison between the simulations when inserting PECs at specific locations in all simulations. The results of simulations demonstrated that the fields calculated as well as controlled to propagate in free space in all dimensions.